Banking Panics and Liquidity in a Monetary Economy - Tarishi Matsuoka; Makoto Watanabe (Tinbergen Institute, 2017)
This paper studies banks' liquidity provision in the Lagos and Wright model of monetary exchanges. With aggregate uncertainty we show that banks sometimes exhaust their cash reserves and fail to satisfy their depositors' need of consumption smoothing. The banking panics can be eliminated by the zero-interest policy for the perfect risk sharing, but the first best can be achieved only at the Friedman rule. In our monetary equilibrium, the probability of banking panics is endogenous and increases with inflation, as is consistent with empirical evidence. The model derives a rich array of non-trivial effects of inflation on the equilibrium deposit and the bank's portfolio.
Keywords: E40; 330; Money Search; Monetary Equilibrium; Banking panics; Liquidity